Is biochar a source or sink for polycyclic aromatic hydrocarbon (PAH) compounds in agricultural soils?. Issue 2 (17th September 2012) - Quilliam, Richard S.; Rangecroft, Sally; Emmett, Bridget A.; Deluca, Thomas H.; Jones, Davey L.
Abstract Polycyclic aromatic hydrocarbons (PAHs) in the environment originate mainly from incomplete combustion of fossil fuels, and pose a significant human health risk. Soils act as environmental sinks for PAHs, as they become strongly absorbed onto soil particles; degradation is mainly driven by microbial catabolism, although it is dependent on PAH bioavailability. There is current interest in burying biochar in soil as a long‐term soil carbon store; however, biochar inherently contains varying levels of PAHs and its application could contaminate soil, and its high sorptive capacity may facilitate the persistence of PAHs in the environment. The aim of this study was to determine the effect of adding biochar to soil on microbial mineralization of PAHs, and to quantify whether or not soils amended with biochar were less likely to leach PAHs. We used contrasting agricultural soils (Eutric Cambisol and Cambic Podzol) spiked with the labelled PAH compound 14C‐phenanthrene and amended with either wood biochar or rice husk biochar. Mineralization was quantified by measuring the release of 14CO2 and simulated rain used to quantify leaching of PAH through biochar‐amended soil. Rice husk biochar had higher concentrations of PAHs (64.65 mg kg−1) than wood biochar (9.56 mg kg−1), and both soil types contained quantifiable levels of PAHs. However, soil that had contained biochar for 3 years had significantly higher levels of PAH (1.95 mg kg−1) compared to unamended soil (1.13 mg kg−1). PAH catabolism in soil was reduced when amended with biochar, although biochar amendment did not consistently decrease PAH leaching. Biochar‐mediated inhibition of PAH mineralization is a consequence of increased sorption and reduced bioavailability. Before large scale biochar addition to soils is adopted, future work is needed to address the dynamic between sorbent saturation and microbial activity and how this relates to the concentration of PAHs in soil solution and their persistence in the environment.